2014
DOI: 10.1007/s40263-014-0216-9
|View full text |Cite
|
Sign up to set email alerts
|

Post-Injection Delirium/Sedation Syndrome in Patients Treated with Olanzapine Pamoate: Mechanism, Incidence, and Management

Abstract: Second-generation antipsychotics (SGAs) are a mainstay in the treatment of patients with schizophrenia. However, continuity in intake of the prescribed medication has been one of the greatest challenges in these patients. One option to improve medication adherence is to prescribe depot or long-acting injectable formulations (LAIs) of antipsychotics. Following risperidone, several other SGAs have been introduced as LAIs. Olanzapine pamoate, paliperidone palmitate, and aripiprazole are the new-generation LAIs, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 33 publications
(65 reference statements)
0
23
0
Order By: Relevance
“…While the profile of side effects corresponds to that observed in short-acting oral formulations of the respective drugs, some other adverse events associated with LAI administration, in addition to injection site complications, may occur. For example, post-injection syndrome has been associated with LAI olanzapine pamoate 34. The potential risk of this serious medical condition, most likely caused by an accidental overdose, requires all patients treated with olanzapine LAI to be monitored for three hours after drug administration.So far, there are only two published studies (one retrospective cohort study, one randomised double-blind trial) comparing efficacy of first-generation (FGA) and second-generation (SGA) LAI 35,36.…”
mentioning
confidence: 99%
“…While the profile of side effects corresponds to that observed in short-acting oral formulations of the respective drugs, some other adverse events associated with LAI administration, in addition to injection site complications, may occur. For example, post-injection syndrome has been associated with LAI olanzapine pamoate 34. The potential risk of this serious medical condition, most likely caused by an accidental overdose, requires all patients treated with olanzapine LAI to be monitored for three hours after drug administration.So far, there are only two published studies (one retrospective cohort study, one randomised double-blind trial) comparing efficacy of first-generation (FGA) and second-generation (SGA) LAI 35,36.…”
mentioning
confidence: 99%
“…3 Current data regarding occurrence, development, manifestation, treatment, and outcome of PDSS are still limited. In a review article published in CNS Drugs 2015, the authors claim that only one case of PDSS has been mentioned in connection with OLAI since the last clinical trial ended in August 2008, 11 whereas a recent study based on postmarketing safety studies and spontaneous reports found a total of 338 PDSS events between March 1, 2009, and March 1, 2014. 3 Regulatory authorities have established risk management mitigation programs.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of PDSS ultimately resulted in the European label for olanzapine LAI having a risk minimization plan associated with it, the key elements being a 3-hour observation period and for patients to be accompanied home at the end of this 3-hour time period 3. In 2013, the European Medicines Agency announced that the safety signal of olanzapine LAI was sufficient to warrant the removal of the requirement of patients to be accompanied home, but the mandatory stipulation of the 3-hour observation period still remains 3,5…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, the European Medicines Agency announced that the safety signal of olanzapine LAI was sufficient to warrant the removal of the requirement of patients to be accompanied home, but the mandatory stipulation of the 3-hour observation period still remains 3,5…”
Section: Introductionmentioning
confidence: 99%